Implementasi Evaluasi Pembelajaran Berbasis Digital Di Sekolah Dasar Bakti Mulya 400 Jakarta - Lil Yusro; Delia Sufitri; Halimatussakdiah .; Muhammadi .; Ranti Meizatri (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to evaluate the implementation of digital-based learning at Bakti Mulya 400 Elementary School, South Jakarta, specifically in the aspect of learning evaluation utilizing digital technology. The transformation of education in the digital era demands a paradigm shift in the learning evaluation system, from conventional to technology-based. The research method used was field observation with a descriptive qualitative approach. Data were collected through direct observation and in-depth interviews with teachers and school officials on October 20, 2025. The research instruments included observation guidelines, interview guidelines, field notebooks, and documentation tools. Data were analyzed using descriptive qualitative analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the school has systematically implemented digital evaluation using the Google Forms platform for daily tests, Quizizz for interactive quizzes, and Kahoot for formative evaluation. The implementation includes formative and summative assessments integrated with Zoom-based learning using English in accordance with the Cambridge curriculum. Digital evaluation offers significant benefits in terms of time efficiency, automated and accurate results, increased student motivation, digital literacy development, and support for the paperless concept. However, obstacles have been identified, such as limited digital devices, dependence on a stable internet connection, teachers' varying technological skills, the risk of technical disruptions, reduced direct interaction, and the need for intensive mentoring for lower-grade students. The study concluded that the implementation of digital-based learning evaluation at Bakti Mulya 400 Elementary School has been effective, supported by adequate infrastructure and strong school commitment. However, improvements in technological facilities and ongoing development of teachers' ICT competencies are needed to optimize 21st-century learning.